The Application of Law of Necessity (Ḋarūrah wa Ḥajjah) on Payment of Interest Based Loans: A Review of the Verdicts of Jurisprudential Academies - Mujeeb ur Rehman; Ghulam Shams Ur Rehman (Journal of Islamic and Religious Studies, 2020)
The prohibition of Interest (Riba), which is a major element of the current financial system, is stated in the Qur'an and Hadith with certainty and clarity. The unavailability of credit facility at the individual level forces any person or entity to turn to financial institutions, where loans are provided on an interest basis. What is the ruling on taking an interest-bearing loan in such a situation? Can interest be borrowed based on necessity? Due to the importance of the issue, various jurisprudential academies have offered their views on it. No comprehensive review can be found in the available literature on necessity and interest in the views of jurisprudential academics on the application of the principle of necessity in the payment of interest-based loans. This article seeks to fill this gap. In this article, after a brief explanation of the concepts of necessity and interest, the views of jurisprudential academies on interest-based loans on need basis has been recorded. Furthermore, the article critically examines how these academies have applied the principle of necessity to need basis interest loans.